Corneal and Conjunctival Sensitivity in Patients With Dry Eye: The Effect of Topical Cyclosporine Therapy - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2010)
Purpose: To evaluate changes in mechanical sensitivity of cornea and conjunctiva in patients with dry eye disease unresponsive to artificial tears therapy and to investigate the effect of topical cyclosporine therapy on sensitivity of the ocular surface. Methods: Thirty-seven patients with dry eye disease and 35 healthy control subjects were enrolled to this prospective study. All patients included in the study completed a 3-month run-in period of using nonpreserved artificial tear supplements, but all failed to achieve adequate subjective or objective improvement. Patients were then instructed to use topical cyclosporine A 0.05% twice a day. Pre- and posttreatment (1, 3, and 6 months) evaluations included, corneal and conjunctival sensitivity testing with the Cochet-Bonnet esthesiometer, Subjective symptom scoring, fluorescein and lissamine green staining, Schirmer test, and tear breakup time (BUT). Results: Conjunctival and corneal sensitivities were significantly lower in patients with dry eye compared with controls (P < 0.0001). In patients with dry eye, corneal sensitivity correlated positively with conjunctival sensitivity and negatively with ocular surface staining scores. Conjunctival sensitivity correlated negatively with the duration of dry eye disease, the total symptom severity score, and the severity of dryness symptom and positively with Schirmer test and tear BUT. Corneal and conjunctival sensitivities did not change significantly after artificial tear therapy (P > 0.05). After topical cyclosporine, statistically significant improvements from baseline were observed in corneal sensitivity at 3- and 6-month visits (P < 0.001). For conjunctival sensitivity, statistically significant improvements from baseline were seen at all follow-up visits (P < 0.0001). Topical cyclosporine treatment also led to significant improvements in symptom scores, Schirmer test, tear BUT, and ocular surface staining scores (P < 0.0001). Conclusions: The mechanical sensitivity of cornea and conjunctiva to tactile stimulus is reduced in patients with dry eye. Our findings suggest that topical cyclosporine may be effective in improving this reduced mechanical sensitivity of the ocular surface.
Keywords: corneal and conjunctival sensitivity; cyclosporine; dry eye; Cochet-Bonnet esthesiometer; Sjogren syndrome; NERVE GROWTH-FACTOR; PRIMARY SJOGRENS-SYNDROME; FLOW-CYTOMETRIC ANALYSIS; KERATOCONJUNCTIVITIS SICCA; OPHTHALMIC EMULSION; IMMUNOPHILIN LIGANDS; INFLAMMATORY MARKERS; CONFOCAL MICROSCOPY; SENSORY GANGLIA; TEAR FLUID